ACQUISITION OF RARE EARTH MINERALS FROM MALAYA IN VIOLATION OF EXPORT CONTROL LAWS FOR JAPAN’S ATOMIC RESEARCH DURING WORLD WAR II - Marina Abdul Majid, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
During World War II (WWII) from 1941-1945, the Japanese sought to obtain uranium and thorium from Malaya meant for its atomic research. This may violate international export controls or the domestic laws of the United States (US) and the United Kingdom (UK). The main objective of this study is to investigate the extent of the Japanese acquisition of uranium and thorium in Malaya for its atomic research during WWII which may or may not have violated international or domestic export control laws of the US and UK. This qualitative study used a textual analysis for interpreting bilateral and trilateral agreements to secure uranium and thorium, the export control laws of the US and UK, and a case law. Other documentation concerning Japanese procurement of amazing in Malaya was referred. Secondary resources of books, book chapters, conference papers, journal articles, newspapers, magazines, and internet materials were also analyzed through content analysis. The write-up for this study is narrative as this study relates to history, law, and security studies. The results of this study indicate the Japan Nitrogen Company based in Malim Nawar had produced carbide, ammunition and ammonia. While this company’s branch in Hŭngnam, North Korea had been scouting for minerals for Japan’s atomic research, it is unknown if the unit in Malaya also played the same role. Amang was shipped to Japan for the extraction of monazite which in turn returned thorium and uranium were used for atomic research but some were sunk at sea or confiscated as war bounty by the US. Penang Island became a transit point for uranium sent by the Germans to the Japanese. The US and the UK export control laws were the most applicable in restricting Japan from acquiring uranium and other minerals for atomic research as international controls were just emerging and applicable among a few selected countries to yet become an accepted norm multilaterally.